Penerapan Metode CLCK untuk Meningkatkan Kualitas Guru dalam Menyusun RPP melalui Pembinaan Supervisi oleh Kepala Sekolah di SDN 3 Pandak Gede - Murjani, Ni Gusti Ayu Made Anom (Jurnal Pendidikan Dewantara, 2023)
This study aims to improve the quality of teachers in developing lesson plans through coaching by supervisors using the CLCK method. To achieve this goal, action research was conducted on teachers at SD Negeri 3 Pandak Gede in the 2022/2023 even semester, totaling 8 teachers. This research was conducted in two learning cycles. The method used was the CLCK method which consists of four main steps, namely: 1) Example, the researcher provides an example of the correct lesson plan to the teacher; 2) Train, the researcher provides practice in preparing the correct lesson plan to the teacher; 3) Try, the researcher provides an opportunity for teachers to try to develop lesson plans independently; and 4) Develop, the teacher develops the lesson plans that have been made in accordance with the assessment system carried out. The object of research is the quality of teachers in developing lesson plans. To measure the quality of teachers in developing lesson plans, lesson plan product observation guidelines were used. The data were analyzed using descriptive analysis using the success criteria of action if the quality of teachers in preparing lesson plans. Based on the results of the research conducted, it can be concluded that coaching by supervisors through the CLCK program can improve the quality of teachers in preparing lesson plans at SD Negeri 3 Pandak Gede. The results of the data analysis of the second cycle of action showed that the quality of teachers in preparing lesson plans had an average of 88 with a very good category. It appears that 50% of teachers (4 teachers) have the ability to develop very good lesson plans; and 50% (4 teachers) have the ability to develop good lesson plans. To achieve optimal results in supervision activities, supervisors in carrying out coaching for mentored teachers should apply the principle of friendship so that there is no impression of being supervised and supervising. This will provide openness for teachers in conveying the obstacles faced in carrying out the learning process.